Semantic displacement of the crucifixion of Jesus Christ in contemporary painting: عبد الحمزة عبد الأمير الكلابي، حيدر عبد الأمير رشيد الخزعلي (Al-Academy, 2016)
The search consists of four chapters, which are as follows: -First Chapter,The research shows the problem and the importance and its need, its aim and limits are to identify the terms of it consist. The problem of the research has been identified by answering the following question:How to representthe significant displacement of the Crucifixion of Jesus Christ in contemporary drawing? ,The aim of the research also has been discussed around what it represents: The significant displacement of the Crucifixion of Jesus Christ in contemporary drawingshows. As for the research limits .the portress which are taken from a variety of sources, and the period of time of the year (1945-2008).fearst chapter;The theoretical framework and previous studies, where the theoretical framework includes three topics, the first topic discusses the understanding of the significant. The second topic discusses the understanding of the displacement and its role title. The third topic it was topic it has been indicated in the crucifixion of Christ which is been mentioned in sacred texts with a statement of how they represented on the basis of indications erosion in visual texts matched with it and committed to pragmatism. Then the researcher included a number of indicators theoretical framework: Third Chapterincludes the procedures of the research which consist research assemblywhere it has reached(106)of richlyartworks of the significant crucifixion. Research's samples was identified by (4) artworks, research tool, Research approach, it is a descriptive approach in a manner of content analysis, means of statistical and mathematicaland analysis of the research sample.The fourth chapter includes the research results, and its conclusions, recommendations, and proposals. The most important findings of the researcher as follows:1-Artists use more than one mechanism within the significant frequently, andthat gave it the same as the led as it been used a single machine, which is the significant displacement, which reflects the extent of freedom exercised by the artist.2-The largest number of types of indications came from comprehensive negative kind, what indicates a lack of orientationintently of the artist consecration and spreading the ideological principles by utilizing the visual text, but on the contrary it completely. 3-When focusing on the artist's works in highlighting the significance of what other without. That would negatively affect the other indications in the same text